PENERAPAN MODEL DISCOVERY LEARNING DALAM PROSES PEMBELAJARAN ONLINE UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PESERTA DIDIK KELAS XII MIPA AMAZON SMA ZION - Hendrik Karewangan; Demitrius Jonathan (Universitas Papua, Manokwari, Indonesia, 2020)
AbstractThis classroom action research aims to find out how the application of the discovery learning model in the online learning process to improve the activity and learning result of class XII MIPA Amazon Zion Senior High School students in the 2020/2021 academic year on alkane derivatives. Using the Kemmis and Mc Taggart model with stages (1) planning, (2) action, (3) observation, and (4) reflection. The research subjects were 34 students of class XII MIPA Amazon SMA Zion. The research data were obtained by using observation sheets and learning result tests. The research data were analyzed by using descriptive statistical analysis (percentage of learning activities and mastery of learning result). The results showed that: (1) the average percentage of students' learning activities increased from 46.62% (less active) in the first cycle to 77.50% (active) in the second cycle, (2) the percentage of students' complete learning result. students experienced an increase from 44.12% in the first cycle to 76.47% in the second cycle.Keywords: Learning activities, discovery learning, learning result, online learning.